In-situ two-step Raman thermometry for thermal characterization of monolayer graphene interface material - Zhao, Wenqiang; Chen, Wen; Yue, Yanan; Wu, Shijing (Applied thermal engineering, 2017)
An in-situ two-step Raman thermometry is developed to measure both interfacial thermal conductance between graphene and substrate, and in-plane thermal conductivity of graphene. [Display omitted] •In-situ two-step Raman method is developed for interfacial thermal characterization.•Both in-plane thermal conductivity and interface thermal conductance can be characterized.•An unconstrained graphene/SiO2 interface material is successfully measured.•Small interface thermal conductance and in-plane thermal conductivity are obtained. To date, accurate thermal property measurement of atomic-layer interface materials still remains as a challenge due to the extreme dimension of sample’s size and limitation of instruments. Raman thermometry emerges as the sole technique for direct measurement of unconstrained graphene interfacial thermal transport. In this work, an in-situ two-step Raman thermometry is developed to measure both interfacial thermal conductance between graphene and substrate, and in-plane thermal conductivity of supported graphene. This two-step Raman approach incorporates the first step: joule-heating experiment for interfacial thermal conductance characterization and the second step: laser-heating experiment for thermal conductivity measurement. Thermal conductance between monolayer graphene and SiO2 is characterized as 340-80+327W/m2K which is much smaller than reported values of sandwiched graphene interface structures, but agrees well with other unconstrained graphene interface structures. The in-plane thermal conductivity of supported graphene is obtained as 179-86+111W/mK. This value is consistent with previously reported data for thermal transport of supported graphene structures, which can be explained by phonons leakage and significant scattering at the interface. The successful measurement of graphene/SiO2 interfacial thermal properties proves that this technique can be well applied to graphene-like atomic-layer materials with Raman-active optical mode.